SPANISH MEDIA DISCOURSE IN THE CONTEXT OF CROSS CULTURAL COMMUNICATION - Zaliesnova Оlena (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article is in essence the research of the Spanish media discourse in view of the modern information space globalization. Various papers related to the language functioning in mass communication that were published on a regular basis in the second half of the XX century created adequate prerequisites for study of the media discourse. As of today information is considered to be a consumer good that retains popularity. New mass communication media emerge to satisfy the interests of the target audience of various ages, professions and personal preferences. The infrastructure of the transnational satellite television resulted in a sustainable cultural consolidation accompanying the globalization process that also involves other mass media. Mass communication includes not only dissemination of information but also organization and aggregate of processes & products of speech production in its richness and complexity of their interaction that can affect the society in any way. Internationalization of any events, news, messages is a complex process of cross-cultural communication in the modern times of globalization. Constant development of information and communication technologies results in rapid increase of the text volumes that are broadcasted via mass media using multiple national languages in the world information space and thus the modern media discourse requires constant participation of translators in the process of producing media products. __________ References: • Gal’perin, R. Tekst kak ob#ekt lingvisticheskogo issledovanija [Text as an object of linguistic research], 4-e izd., stereotip. (Moskva: KomKniga, 2006), 144 (In Russian). • Dobrosklonskaja, G. Voprosy izuchenija mediatekstov (opyt issledovanija sovremennoj anglijskoj mediarechi) [The problems of studying media texts (experience in the study of modern English media speech)], 4-e izd., stereotip. (Moskva: Editorial URSS, 2005), 288 (In Russian). • Dobrosklonskaja, G. Medialingvistika: sistemnyj podhod k izucheniju jazyka SMI: sovremennaja anglijskaja mediarech’ [Media linguistics: a systematic approach to the study of the language of the media: modern English media speech] (Moskva: Flinta, 2008), 263 (In Russian). • Kirillova, B. Mediakul’tura: ot moderna k postmodernu [Media culture: from modern to postmodern] (Moskva: Akademicheskij proekt, 2005), 448 (In Russian). • Sovremennyj mediatekst: uchebnoe posobie [Modern media text: study guide] (Omsk, 2011), 414 (In Russian). • Bretones,María Trinidad. Los medios de comunicación de masas: desarrollo y tipos (Universidad de Barcelona, 2008), • Martín Ruano, María Rosario, Vidal Claramonte, África. Traducción, medios de comunicación, opinión pública (Granada: Editorial Comares. Colección Interlingua 156, 2016), 336.